The effect of foreign direct investment on economic growth in Indonesia: A case study using secondary data for 1995-2023 - Engelica, Heni; Wulansari, Annisa Retno; Muthoharoh, Faridlotun; Azzahra, Fayi Faizah; Istiqomah, Nurul; Cantikasari, Selvia (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Foreign Direct Investment (FDI) is one of the key instruments for driving economic growth in most countries, including Indonesia. FDI refers to a type of investment in which foreign entities directly invest capital into an economic entity in the host country. Foreign Direct Investment has become an essential source of external financing for Indonesia and serves as one of the primary funding sources. Therefore, this study aims to comprehensively analyze the impact of FDI on Indonesia’s economic growth over the period 1995–2023. Methods: This study employs a quantitative research approach with multiple linear regression analysis. This model is chosen because it allows for the measurement of the simultaneous influence of multiple independent variables on a single dependent variable, namely economic growth. The study utilizes processed secondary data supplemented with time series data, including Gross Domestic Product (GDP) growth, foreign investment, inflation rate, exchange rate, government expenditure, and poverty levels. Findings: The findings indicate that FDI positively and significantly affects Indonesia’s economic growth. FDI enhances production capacity, increases efficiency, and facilitates technology transfer, contributing to national productivity. Additionally, a stable exchange rate and controlled inflation support economic development. However, the exchange rate negatively affects economic growth, suggesting that fluctuations may hinder investment and economic activities. Meanwhile, inflation is found to have no significant impact on GDP growth, possibly due to economic stability, political events, or government interventions during the study period. Conclusion: Based on the research findings, it can be concluded that FDI plays a significant role in driving economic growth in Indonesia. However, exchange rate fluctuations pose a challenge that should be managed to ensure economic stability. Novelty/Originality of this article: The novelty of this research lies in its comprehensive time-series analysis covering nearly three decades, providing insights into the long-term relationship between FDI and economic growth in Indonesia.